Analisis Pola Pikir (Mindset), Penilaian Kerja Dan Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Kecamatan Batu Mandi Kabupaten Balangan Kalimantan Selatan - Ermina Suriyanti (JURNAL KINDAI, 2020)
Ermina Suriyanti, Npm. 1811.32202.4733, Analysis Of Mindset Patterns, Assessment Of Work And Leadership On Performance In Office Of Batu Mandi District Balangan, Kalimantan Selatan, Bod Guidance Of Rosadiro Cahyono And Yudi Rahman, 2020. The aim of this research is to find out and analyze the influence of mindset, job evaluation and leadership patterns partially on ASN performance, to know and analyze the influence of mindset, work assessment and leadership patterns simultaneously on performance ASN and to find out among the mindset variables, work assessment and leadership patterns that have a dominant influence on ASN performance at the Batu Mandi District Office in Balangan Regency. The population and sample in this study were 31 sub-district employees. The data processing technique used is a quantitative method with the application of SPSS multiple regression analysis. The first hypothesis testing is known that the mindset, work appraisal and leadership pattern partially on the ASN performance. The second hypothesis testing is also known that the mindset variable, work assessment and leadership pattern simultaneously on the ASN performance in Batu Mandi District Office Balangan District and in the third hypothesis testing the mindset variable that has a dominant influence on ASN performance at the Office Batu Mandi District of Balangan Regency. Keywords: Mindset, Work Assessment, Leadership and The performance